Sequence

Algebra Level 5

S = 5 1 × 3 × 7 + 7 3 × 5 × 9 + 9 5 × 7 × 11 + S=\dfrac{5}{1 \times 3 \times 7}+\dfrac{7}{3 \times 5 \times 9}+\dfrac{9}{5 \times 7 \times 11}+\cdots

If 45 S = n 2 + 1 45S = n^2+ 1 , where n n is a positive integer, find n n .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ikkyu San
May 16, 2016

S = 5 1 × 3 × 7 + 7 3 × 5 × 9 + 9 5 × 7 × 11 + = i = 1 2 i + 3 ( 2 i 1 ) ( 2 i + 1 ) ( 2 i + 5 ) = i = 1 1 3 ( 2 ( 2 i 1 ) ( 2 i + 1 ) + 1 ( 2 i + 1 ) ( 2 i + 5 ) ) = 1 3 ( i = 1 2 ( 2 i 1 ) ( 2 i + 1 ) + i = 1 1 ( 2 i + 1 ) ( 2 i + 5 ) ) = 1 3 [ lim k i = 1 k ( 1 2 i 1 1 2 i + 1 ) + lim k i = 1 k 1 4 ( 1 2 i + 1 1 2 i + 5 ) ] = 1 3 [ lim k ( 1 1 2 k + 1 ) + 1 4 lim k ( 1 3 + 1 5 1 2 k + 5 ) ] = 1 3 [ 1 + 1 4 ( 8 15 ) ] = 1 3 ( 17 15 ) = 17 45 45 S = 17 = 4 2 + 1 \begin{aligned}S&=\dfrac5{1\times3\times7}+\dfrac7{3\times5\times9}+\dfrac9{5\times7\times11}+\cdots\\&=\displaystyle\sum_{i=1}^{\infty}\dfrac{2i+3}{(2i-1)(2i+1)(2i+5)}\\&=\displaystyle\sum_{i=1}^{\infty}\dfrac13\left(\dfrac2{(2i-1)(2i+1)}+\dfrac1{(2i+1)(2i+5)}\right)\\&=\dfrac13\left(\displaystyle\sum_{i=1}^{\infty}\dfrac2{(2i-1)(2i+1)}+\displaystyle\sum_{i=1}^{\infty}\dfrac1{(2i+1)(2i+5)}\right)\\&=\dfrac13\left[\displaystyle\lim_{k\to\infty}\sum_{i=1}^k\left(\dfrac1{2i-1}-\dfrac1{2i+1}\right)+\displaystyle\lim_{k\to\infty}\sum_{i=1}^k\dfrac14\left(\dfrac1{2i+1}-\dfrac1{2i+5}\right)\right]\\&=\dfrac13\left[\displaystyle\lim_{k\to\infty}\left(1-\dfrac1{2k+1}\right)+\dfrac14\displaystyle\lim_{k\to\infty}\left(\dfrac13+\dfrac15-\dfrac1{2k+5}\right)\right]\\&=\dfrac13\left[1+\dfrac14\left(\dfrac8{15}\right)\right]\\&=\dfrac13\left(\dfrac{17}{15}\right)\\&=\dfrac{17}{45}\\45S&=17=4^2+1\end{aligned}

Thus, n = 4 n=\boxed4 .

noob. i didn't understand the step no. 4 from below.

Arshad Ahmed - 8 months, 4 weeks ago
Chew-Seong Cheong
May 17, 2016

S = 5 1 × 3 × 7 + 7 3 × 5 × 9 + 9 5 × 7 × 11 + = n = 0 2 n + 5 ( 2 n + 1 ) ( 2 n + 3 ) ( 2 n + 7 ) By partial fractions = n = 0 ( 1 3 ( 2 n + 1 ) 1 4 ( 2 n + 3 ) 1 12 ( 2 n + 7 ) ) = 1 3 n = 0 1 2 n + 1 1 4 ( n = 0 1 2 n + 1 1 ) 1 12 ( n = 0 1 2 n + 1 1 1 3 1 5 ) = ( 1 3 1 4 1 12 ) n = 0 1 2 n + 1 + 1 4 ( 1 ) + 1 12 ( 1 + 1 3 + 1 5 ) = ( 0 ) n = 0 1 2 n + 1 + 1 4 + 1 12 ( 23 15 ) = 17 45 \begin{aligned} S & = \frac{5}{1 \times 3 \times 7}+\frac{7}{3 \times 5 \times 9}+\frac{9}{5 \times 7 \times 11}+\cdots \\ & = \sum_{n=0}^\infty \frac{2n+5}{(2n+1)(2n+3)(2n+7)} \quad \quad \small \color{#3D99F6}{\text{By partial fractions}} \\ & = \sum_{n=0}^\infty \left( \frac{1}{3(2n+1)} - \frac{1}{4(2n+3)} - \frac{1}{12(2n+7)}\right) \\ & = \frac{1}{3} \sum_{n=0}^\infty \frac{1}{2n+1} - \frac{1}{4} \left( \sum_{n=0}^\infty \frac{1}{2n+1} - 1 \right) - \frac{1}{12} \left( \sum_{n=0}^\infty \frac{1}{2n+1} - 1 - \frac{1}{3} - \frac{1}{5} \right) \\ & = \left( \frac{1}{3} - \frac{1}{4} - \frac{1}{12} \right) \sum_{n=0}^\infty \frac{1}{2n+1} + \frac{1}{4}(1) + \frac{1}{12}\left(1+\frac{1}{3}+\frac{1}{5} \right) \\ & = \left( 0 \right) \sum_{n=0}^\infty \frac{1}{2n+1} + \frac{1}{4} + \frac{1}{12}\left(\frac{23}{15} \right) \\ & = \frac{17}{45} \end{aligned}

45 S = 17 = 16 + 1 = 4 2 + 1 n = 4 \implies 45S = 17 = 16 + 1 = 4^2 + 1 \\ \implies n = \boxed{4}

Did the exact same

Aditya Kumar - 5 years ago

Can you explain how you broke into step 4 of your solution where you have written 1 / 3 n = 0 ( 1 / ( 2 n + 1 ) ) 1 / 4 ( n = 0 1 / ( 2 n + 1 ) 1 ) 1 / 12 ( n = 0 1 / ( 2 n + 1 ) 1 1 / 3 1 / 5 ) 1/3 \sum_{n=0}^{\infty}(1/(2n+1)) -1/4( \sum_{n=0}^{\infty}1/(2n+1) - 1) - 1/12(\sum_{n=0}^{\infty}1/(2n+1) - 1 - 1/3 - 1/5) , all other steps are understandable.

Arnav Das - 5 years ago

Log in to reply

n = 0 1 2 n + 1 = 1 / 1 + 1 / 3 + 1 / 5 + 1 / 7 + 1 / 9 + . . . n = 0 1 2 n + 7 = 1 / 7 + 1 / 9 + . . . = n = 0 1 2 n + 1 1 1 / 3 1 / 5. \displaystyle \sum_{n=0}^{\infty} \frac1{2n+1}=1/1+1/3+1/5+1/7+1/9+ . . .\\ \displaystyle \sum_{n=0}^{\infty} \frac1{2n+7}=1/7+1/9+ . . . \\ \displaystyle =\sum_{n=0}^{\infty} \frac1{2n+1}-1-1/3-1/5.

Niranjan Khanderia - 3 years, 11 months ago
Mayank Singh
May 20, 2016

How much did you score in this AITS

What is AITS?

Mritunjay Mehta - 5 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...